Using Whole-genome Sequencing to Determine the Timing of Secondary Tuberculosis in British Columbia, Canada - Romanowski, Kamila (Clin Infect Dis, 2020)
Combined with epidemiological data, whole-genome sequencing (WGS) can help better resolve individual tuberculosis (TB) transmission events to a degree not possible with traditional genotyping. We combine WGS data with patient-level data to calculate the timing of secondary TB among contacts of people diagnosed with active TB in British Columbia, Canada.